Nuclear Transition Matrix Elements for Double-β Decay Within PHFB Model - Rath, P. K.; Chandra, Ramesh; Chaturvedi, K.; Raina, P. K. (Frontiers in Physics, 2019)
Employing the projected-Hartree-Fock-Bogoliubov (PHFB) approach, nuclear transition matrix elements (NTMEs) have been calculated to study the three complementary modes of β ^-β ^- decay, namely two neutrino % β ^-β ^- (2ν β ^-β ^-) decay, neutrinoless % β ^-β ^- (0ν β ^-β ^-) decay within mass mechanism and Majoron accompanied 0ν β ^-β ^- (0ν β ^-β ^-χ ) decay. Reliability of HFB wave functions generated with four different parametrizations of the pairing plus multipolar type of effective two-body interaction has been ascertained by comparing a number of nuclear observables with the available experimental data. Specifically, the calculated NTMEs M^(2ν ) of 2ν β ^-β ^- decay have been compared with the observed data. Effects due to different parametrizations of effective two-body interactions, form factors and short-range correlations have been studied. It has also been observed that deformation plays a crucial role in the nuclear structure aspects of 0ν β ^-β ^- decay. Uncertainties in NTMEs calculated with wave functions generated with four different parametrizations of the pairing plus multipolar type of effective two-body interaction, dipole form factor and three different parametrizations of Jastrow type of short-range correlations within mechanisms involving light Majorana neutrinos, heavy Majorona neutrinos, sterile neutrinos and Majorons have been statistically estimated.